Carbon Based Nanomaterials for Detection of Heavy Metals and Water Treatment - Mujahid, Fatima; Mujahid, Fizza; Azeem, Subhan; Bakht Muhammad; Azeem, Muhammad Shoaib; Mehwish Rafique; Yasmeen Bano; Maha Dev Makwano; Abdul Samad; Qamar Sajjad (Indus Journal of Bioscience Research, 2025)
This report explores the use of carbon nanoparticles for the detection of heavy metals, highlighting their potential in environmental and industrial applications. Various carbon nanomaterials, such as graphene-based materials, carbon nanotubes, and fullerenes, are employed for the extraction of heavy metals and wastewater treatment. Carbon nanoparticles have gained significant attention as heavy metal detectors and water purifiers due to their high reactivity, large surface area, and unique properties. These characteristics make them ideal for detecting and removing toxic heavy metals from contaminated environments. However, the widespread application of carbon nanoparticles is hindered by challenges such as high production costs, complex synthesis methods, and environmental concerns. Despite these limitations, ongoing research is focused on optimizing the use of carbon nanoparticles in several promising domains. These include nanoelectronics, smart materials, biomedical applications, energy storage and conversion, advanced water treatment systems, and sensing technologies. By addressing the existing challenges and exploring emerging opportunities, carbon nanoparticles have the potential to revolutionize various industries. With continued advancements in their production and functionality, carbon nanoparticles could provide more sustainable solutions for environmental pollution, particularly in the fields of water purification and heavy metal detection. As these technologies evolve, carbon nanoparticles are poised to contribute to a more technologically advanced and environmentally friendly future. Their successful integration into multiple industries could lead to breakthroughs in water treatment and pollution control, further improving environmental sustainability and human health. Carbon nanoparticles offer substantial promise, but overcoming the current challenges is key to unlocking their full potential.